2020
DOI: 10.21577/0103-5053.20200042
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial High-Density Polyethylene (HDPE)/ZnO Nanocomposites Obtained by in situ Polymerization

Abstract: Nanostructured zinc oxide (ZnO) prepared by combustion in solution was used to obtain nanocomposites. The ZnO particles were characterized by Brunauer-Emmett-Teller (BET), X-ray diffraction (XRD), and scanning electron microscopy (SEM), showing crystallite size of 32 nm and a superficial area of 32.6 m 2 g -1 . Nanocomposites with 1, 3, and 5 wt.% of ZnO in the polymeric matrix were obtained using the in situ polymerization of ethylene with catalytic activities between 1500-1700 kg (mol Zr h P E ) -1 . The hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Based on the DSC analysis, the of the polymer was estimated by integrating the area under the endothermic curve (in J/g). This allowed us to estimate the degree of crystallization ( ), according to equation 1 [ 44 ], where the enthalpy of fusion used for 100% HDPE crystallization was 293 J mol −1 [ 45 ]: …”
Section: Resultsmentioning
confidence: 99%
“…Based on the DSC analysis, the of the polymer was estimated by integrating the area under the endothermic curve (in J/g). This allowed us to estimate the degree of crystallization ( ), according to equation 1 [ 44 ], where the enthalpy of fusion used for 100% HDPE crystallization was 293 J mol −1 [ 45 ]: …”
Section: Resultsmentioning
confidence: 99%
“…For ionic zinc, no observed adverse effect level was established at 50 mg/day, and an upper limit of 25 mg/person per day was recommended [ 28 ]. The scientific literature highlights the antimicrobial activity of ZnO NPs against model pathogens, both Gram- positive or Gram-negative strains [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nano ller adding has been approved as an applicable method to reduce dielectric characteristics of certain polymeric substrates [3,4,6,11,[13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Incorporation polyhedral oligomeric silsesquioxane (POSS) hybrid introduced into uorinated poly(ether ether ketone ketone) (FPEEK) polymers can considerably reduce their dielectric constants [19] .…”
Section: Introductionmentioning
confidence: 99%
“…This ε r value was considerably lower than that of PEKK/nano-SiO 2 with 10wt% SiO 2 nano llers [26] . Some researches [17,18,20,24,25] suggested that the signi cant decrease in ε r values for polymer/nano ller compounds is owing to the small ε r of nano llers and/or existent air holes having small ε r (~ 1.0). Some researchers [13,22] proposed that the evident interfacial effect derived from dispersed nano llers could interact, restrain the agility of polar groups in polymer chains, and, hence diminish the polarizability and ε r values.…”
Section: Introductionmentioning
confidence: 99%